Nickel and Chrome Pollutions Identification in the Coastal Area of Kulon Progo, Yogyakarta - Ronaldo Irzon (Badan Geologi, 2017)
Abstract Kulon Progo is located in the southern part of Yogyakarta Special Province, Indonesia. The regency is famous of some tourist beach points. This study discusses the compositiom of beach sand samples in three coastal areas in Kulon Progo: Karangwuni, Glagah, and Congot in relation to environmental issues. Seven samples of four locations were megascopically descripted and analyzed using XRF and ICP-MS for geochemistry contents. Four of samples are beach sands from the surface whilst the others were collected from about 50 cm below surface. Box plots show maximum Cr outlier and minimum most of REE outliers in the group of beach sand samples. Nickel and chrome tenor anomalies were detected in samples from coastline of Karangwuni and Glagah. On the other hand, no Ni and Cr anamalies were indentified in the two samples 200 m from the seashore of Karangwuni nor the two samples near Congot seashore. In the polluted location, the two heavy metals are relatively concentrated in the surface. Two volcanic rock samples from the Andesite domain are selected to trace the origin of the heavy metals. The wastes of basic metal mining in northern Kulon Progo together with urban activities and several industries in Wates were then transported through the Serang River to Indian Ocean. Tidal currents helps the heavy metals to be deposited in the coastal areas near the mouth of Serang River. This study also concluded that folk gold mining activity in Sangon is not the source of Ni and Cr pollution to the coast of Kulon Progo.Keyword: geochemistry, beach sand, Kulon Progo, heavy metals pollution. Sari Kulon Progo berlokasi di bagian selatan Provinsi Daerah Istimewa Jakarta, Indonesia. Kabupaten ini terkenal dengan beberapa lokasi wisata pantai. Studi ini membahas mengenai komposisi pasir pantai pada tiga lokasi pantai di Kulon Progo: Karangwuni, Glagah, dan Congot terkait dengan masalah lingkungan. Tujuh contoh dari empat lokasi penelitian telah dideskripsikan secara megaskopis dan dianalisis kandungan geokimianya menggunakan XRF dan ICP-MS. Empat contoh merupakan pasir pantai yang berasal dari permukaan sedangkan contoh lain berasal dari 50 cm di bawah permukaan. Box plot dengan jelas menunjukkan keberadaan maximum outlier pada Cr dan minimum ourlier pada banyak elemen dari REE pada kelompok contoh pasir pantai. Anomali tinggi nikel dan krom terdeteksi pada seluruh contoh yang berada dekat tepi pantai di Karangwuni dan Glagah. Namun demikian, tidak terdapat anomali Ni dan Cr pada dua contoh yang berasal dari 200 m sebelum tepi pantai Karangwuni maupun dua contoh dari Pantai Congot. Pada titik yang tercemar polusi, dua logam berat ini lebih terkonsentrasi pada bagian permukaan. Dua batuan vulkanik dari wilayah Andesit dipilih dalam menelusuri asal muasal logam berat tersebut. Sampah sisa penambangan logam dasar bersama dengan aktifitas perkotaan dan industri di Kulon Progo telah terbawa oleh aliran Sungai Serang menuju Samudera Hindia. Arus bolak-balik air laut membantu logam berat tersebut terdepositkan di wilayah pantai dekat dengan mulut Sungai Serang. Studi ini turut menyimpulkan bahwa penambangan emas rakyat di Sangon bukan sebagai sumber pencemaran Ni dan Cr di tepi pantai Kulon ProgoKata kunci: geokimia, pasir pantai, Kulon Progo, polusi logam berat